Examining the relationship between sleep quality and depressive symptoms in Korean women engaged in soccer during the coronavirus pandemic - Kim, Young-Jae; Lee, Da-Som; Kim, E-Sack (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic has caused sudden changes to daily lives, such as self-isolation and social distancing, and has negatively affected sleep quality and patterns. The resulting psychological discomfort has caused many Korean women to experience depressive moods. Vigorous physical activity is considered effective in improving sleep quality and alleviating depressive symptoms. As a form of vigorous physical activity, soccer could be used to improve women's mental health. This study aimed to ascertain the effects of playing soccer on sleep quality and depressive symptoms in women. Methods Non-face-to-face questionnaires were administered using Pittsburgh Sleep Quality Index to measure sleep quality and Patient Health Questionnaire-9 to measure depressive symptoms, targeting 200 of 297 soccer-playing Korean women aged 20–50 years, from October 13, 2022, to January 15, 2023. A total of 172 questionnaires administered to soccer participants were used, while 28 with insincere and double or no-responses were excluded. Additionally, 124 samples of non-exercise participants were collected, with the help of “EMBRAIN,” a Korean research and survey company. This study analyzed differences in sleep quality and depressive symptoms, and correlations and multiple regression analysis were performed. Results The soccer group was shown to have a high quality of sleep. In relation to the effect of sleep quality on depressive symptoms, subjective sleep quality, sleep latency, sleep disturbance, use of sleeping pills, and daytime functional disorder had a significant effect. In the relation to the effect of sleep quality on depressive symptoms, significant effect was found in subjective sleep quality, sleep latency, sleep disturbance, and daytime functional disorder of soccer participants, and non-exercise participants displayed significant effect in subjective sleep quality, sleep disturbance, and the use of sleeping pills. Discussion This study examined the effect of soccer participation on sleep quality and depressive symptoms among women. Soccer, which requires high activity and teamwork levels, improves sociability in women by enhancing their sense of belonging, self-confidence, and team spirit.